A Tale of Two Managers: Dunning-Kruger and the Impostor (Journal of Organizational Psychology, 2025)
We have seen them in action. We may have even worked with one, or both contrasting types of managers. The Impostor Manager (IM) is modest and not self-aware of their abilities. Rather, they attribute their success to luck or chance. The Dunning-Kruger (DKM) manager is the opposite. She or he has an over-abundance of confidence in their skills and ability and often assumes the department's success can be attributed to their superior leadership skills. In this paper, the researchers discuss issues surrounding both types of managers and offer recommendations to develop these managers into high-performing leadership team members.
Keywords: organizational psychology; Dunning-Kruger effect; the impostor syndrome; the impostor cycle